PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK (Studi Kasus pada UMKM Kabupaten Klaten): (Studi Kasus pada UMKM Kabupaten Klaten) - Kundala, Manendha Maganitri; Kase, Joni Jerilius; Setyowati, Hasanah (PRIMA EKONOMIKA, 2024)
This study aims to determine the effect of taxpayer awareness on taxpayer compliance inpaying taxes and the effect of knowledge and understanding of tax regulations ontaxpayer compliance in paying taxes. The method used is quantitative research with theobject of research being Micro, Small and Medium Enterprises (MSMEs) in KlatenRegency with 110 respondents obtained. The results of the study showed that the taxawareness variable (X1) had a significant positive impact on tax compliance of MSMEsrecorded in Klaten Regency. The first hypothesis was accepted by the research data,namely that tax awareness had a positive impact on MSME tax compliance. Then, thetax knowledge variable (X2) had a significant positive impact on MSME taxcompliance recorded in Klaten Regency. The second hypothesis was accepted or supportedby the research data, namely that tax knowledge had a positive impact on MSME taxcompliance. In conclusion, there is a good relationship between "Taxpayer Awareness"and "Tax Knowledge" which play a major role in increasing "Tax Compliance" inMSMEs in Klaten Regency. Managing and increasing tax awareness and knowledgetax among MSME taxpayers can be effective steps in efforts to increase the level of taxcompliance in the region.Keywords: Taxpayer; Taxpayer Awareness; Tax Knowledge